Подход к организации контекстного поиска в системе электронного документооборота с применением XML представления фреймовой модели документа - Керносов, М. А. (ХНУРЭ, 2008)
The approach to organization of contextual searching in Electronic Document Management System (EDMS) is offered. For work with electronic document in EDMS is expected using as text, so and formalized presentations of the document. For formalization of document structure the frame-based document model is applied. This model can be easy presented as an XML-document, describing structure of the electronic document and containing contributed in it factographic data. Such XML-presentation allows to organize speediest contextual searching for in formalized presentations of the document due to exception of redundant information.
Keywords: организация контекстного поиска; фреймовая модель документа